(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
The present study explored the effect of fluid intelligence on reading and listening abilities. A total of 50 undergraduate students (age ranging from 20 to 24 years) participated in this study. Data were collected using the shortened version of Raven’s Standard Progressive Matrices, and the tests assessed reading and listening ability. The obtained data were analyzed using an independent sample t-test. Results indicated that individuals with high intelligence outperformed on reading and listening comprehension compared to individuals with low intelligence. However, no significant gender difference was observed in intelligence, reading ability, and listening ability (p > .05). The findings offer crucial allusions for educational institutions in designing the curriculum for students. Jagannath University Journal of Life and Earth Sciences, 9(1): 1-6, 2023 (June)